2015
DOI: 10.5606/kbbihtisas.2015.28863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mean platelet volume and its ratio over platelet count in children with obstructive sleep apnea syndrome

Abstract: Evaluation of mean platelet volume and its ratio over platelet count in children with obstructive sleep apnea syndromeTıkayıcı uyku apne sendromu olan çocuklarda ortalama trombosit hacmi ve ortalama trombosit hacminin trombosit sayısına oranının değerlendirilmesi ABSTRACTObjectives: This study aims to determine the association between obstructive sleep apnea syndrome (OSAS) caused by adenotonsillar hypertrophy and mean platelet volume (MPV) and MPV/platelet count ratio in children, and to evaluate the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 17 publications
1
23
1
Order By: Relevance
“…PLT/MPV, as with MPV, increases in myocardial infarction, anemia, deep vein thrombosis, infective endocarditis, and hepatocellular carcinoma (30). In the present study MPV and PLT/MPV showed no correlation with the eosinophilic and non-eosinophilic group.…”
Section: Crp Nlr Mpv Plt/mpvcontrasting
confidence: 60%
“…PLT/MPV, as with MPV, increases in myocardial infarction, anemia, deep vein thrombosis, infective endocarditis, and hepatocellular carcinoma (30). In the present study MPV and PLT/MPV showed no correlation with the eosinophilic and non-eosinophilic group.…”
Section: Crp Nlr Mpv Plt/mpvcontrasting
confidence: 60%
“…Increased platalet activation may be related to an increase of cardiopulmonary risk in patients with AH. The study of Soyalıç et al [13] have reported that MPV was higher in children with adenotonsillar hypertrophy and that adenotonsillectomy lowers MPV levels in such patients. In contrast, the study of Cengiz et al [14] have evaluated the associations between MPV levels and chronic tonsillitis-AH in children.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In literature, previous studies explored the effect of OSAS on MPV levels. The study of Soyalıç et al 12 have reported that MPV was higher in children with adenotonsillar hypertrophy and that adenotonsillectomy lowers MPV levels in such patients. In contrast, the study of Cengiz et al 13 have evaluated the associations between MPV levels and chronic tonsillitis-AH in children.…”
Section: Discussionmentioning
confidence: 99%